(untitled) (Baghdad Science Journal, 2006)
Been investigating a Pfyrus antigen hepatitis pattern J and Virus-positive rubella viral hepatitis antibodies pattern J. declaration followed by the percentage rate-positive patients of measles Allmana antibodies